2018
DOI: 10.31072/rcf.v9iedesp.598
|View full text |Cite
|
Sign up to set email alerts
|

Constipação Intestinal: Tratamento Com Fitoterápicos

Abstract: A constipação intestinal (CI), também chamada de obstipação intestinal, é determinada pela dificuldade frequente ou eventual de defecação, causando desconforto e outros transtornos ao indivíduo. Trata-se de uma sintomatologia e não de uma patologia específica. Em razão do baixo número de laxantes sintéticos, vêm sendo muito utilizado os laxantes de origem vegetal, devido sua variedade, sendo assim, múltiplas plantas medicinais servem de fonte alternativa de fármacos. O objetivo desse artigo é esclarecer os asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
1
2
0
4
Order By: Relevance
“…When investigating the type of feces according to the Bristol scale, a higher frequency of stool type 3 was noticed, corroborating the results of several studies 4,16,17 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…When investigating the type of feces according to the Bristol scale, a higher frequency of stool type 3 was noticed, corroborating the results of several studies 4,16,17 .…”
Section: Discussionsupporting
confidence: 87%
“…In order to be diagnosed with an intestinal constipation, the individual must show at least two or more manifestations of the Rome IV criteria within a period of three months. In this study, it was observed that most participants had intestinal constipation 4,17 , with a predominance of lumpy or hard stools and a sensation of incomplete evacuation. Such result can also be found in several studies on the prevalence of intestinal constipation 18,19 .…”
Section: Discussionmentioning
confidence: 66%
“…Other important conditions are fecal impaction and constipation, indicated by several studies as an important risk factor and related to incontinence [18][19][20][21] . Constipation is classified into primary and secondary, and its primary causes are associated with nonrelaxation of the anorectal PFM, inadequate fiber intake, colon inertia, incorrect diet, poor control of bowel habit; secondary causes involve neurological factors, caused by traumatic or systemic neuropathies, endocrine diseases, and drug treatments 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Outras condições importantes são a impactação fecal e a constipação, apontadas por diversos estudos como importante fator de risco e relacionado a incontinência [18][19][20][21] . A constipação intestinal se classifica em primária e secundária, e suas causas primárias estão associadas ao não relaxamento da musculatura anorretal do assoalho pélvico, consumo inadequado de fibras, inércia colônica, alimentação incorreta, mau controle do hábito da evacuação; as causas secundárias envolvem fatores neurológicos, provocados por neuropatias traumáticas ou sistêmicas, doenças endócrinas e tratamentos medicamentosos 22 .…”
Section: Discussionunclassified